Analysis of Consumer Protection for Medicines and Foods That Are Not Registered with BPOM - Bayu Nugroho; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2023)
The author writes a journal by analyzing and explaining BPOM's goals in enforcing and enforcing consumer protection regulations based on the Consumer Protection Administration Law No. 8 of 1999. In this case the Food and Drug Supervisory Agency (BPOM) has a role and responsibility for the circulation of each drug and food product in the framework of granting permits for each drug and food product circulating in the community. The Food and Drug Supervisory Agency (BPOM) is a government agency responsible for drug and food control. The Consumer Protection Law prohibits the manufacture of goods for the general public, namely the types of goods listed in Law Number 8 of the Republic of Indonesia concerning Consumer Protection for the purpose of increasing knowledge and skills (1999 Consumer Protection Law). violated because of the indiscriminate nature of the company's behavior. and independence of consumer self-defense. Protect the dignity of customers by protecting them from harmful use and oversupply of services. Empowering consumers by letting them choose the products they want to buy and asserting their legal rights.